Association between biopsy method and development of peritoneal metastases in perihilar cholangiocarcinoma. Issue 6 (June 2022) - Aveson, Victoria G.; Ilagan, Crisanta H.; Chou, Joanne F.; Gönen, Mithat; Balachandran, Vinod P.; Drebin, Jeffrey A.; Jarnagin, William R.; Wei, Alice C.; Kingham, T. Peter; D'Angelica, Michael I.
Abstract: Background: In patients with perihilar cholangiocarcinoma (PHC), there is concern that transperitoneal (TP) biopsy may seed tumor in the peritoneal cavity, increasing risk of peritoneal metastases (PM). Methods: A retrospective review of patients undergoing surgery for PHC (1991–2014) was performed. Clinicopathologic characteristics and incidence of PM at the time of index surgery, and one and two years after surgery were compared in patients who did vs. did not undergo TP biopsy. Results: Among 262 patients who underwent surgery, 37 had undergone TP biopsy, and 225 had undergone intraluminal biopsy or had no biopsy. No differences in demographic or clinicopathologic characteristics were noted between groups. The incidence of PM at surgery was not significantly different between TP and non-TP biopsy patients (5.4% vs. 7.6%, p > 0.9). Among 243 patients who did not have PM at surgery, the cumulative incidence of PM in the TP and non-TP biopsy groups were not different at one year (11.4% [95%CI 3.5–24.4] vs. 10.8% [95%CI 7.0–15.5]) or two years (20.3% [95%CI 8.7–35.2] vs. 20.1% [95%CI 14.9–25.9]) (p = 0.7). Discussion: Although PM commonly occurs in patients with PHC, TP biopsy was not associated with higher incidence of PM at surgery or at one or two years after surgery.